(untitled) (Research, Society and Development, 2022)
In the literature, several authors argue that classes based on the merely expository mode can be a major obstacle in the teaching and learning process, since this teaching methodology can cause demotivation in students, leading to an attention deficit during classes. To overcome these obstacles, alternative teaching methodologies, such as the use of experimental classes, emerge as a methodological alternative of great impact on the guiding process of teaching and learning, allowing to facilitate the contextualization of the content to be learned by students. In this sense, using simple and low-cost materials, such as instant dry yeast, sugar, xylitol and powdered extract of dry Stevia leaves, the main objective of this article is to propose an experimental class in order to facilitate learning. of students in the discipline of Biology in High School, regarding the mechanism of anaerobic cellular respiration (alcoholic fermentation) of yeasts (Saccharomyces cerevisiae). As main results, students will be able to perceive that only the treatment of cup number 2 (warm water, dry biological yeast and common sugar), a reaction will occur, with a great fermentative metabolism of the yeasts, with the formation of ATP, air bubbles ( release of carbon dioxide) on the surface of the glass and ethanol, which will be noticeable through a characteristic sour aroma. In this way, we believe that the proposed experimental activity, together with the discussions and problematizations guided by the teacher, can impact teaching in a more positive way, facilitating student learning, in addition to promoting the perspective of scientific experimentation.